Głos Solidarności . no. 2, 1988 - Ciechanowicz-, Sarata, Aleksandra; Lipski, Paweł; Wiśniewski, Walerian; Drewnicz, Dariusz; Marszal, Krzysztof; Mirecki, Tadeusz ([s.n.], 1988)
Print run: 4000-15000 copies